Kontribusi BUMDes Harapan Kita terhadap kesejahteraan masyarakat dalam perspektif ekonomi syariah: Kajian maslahah di Desa Loa Kulu Kota Kabupaten Kutai Kartanegara - Santi Eka Panasiah; Muhammad Ravi Irdi Abdillah (AL-Muqayyad, 2026)
Village economic development requires local institutions that are trustworthy, fair, and oriented toward public benefit. This study analyzes the contribution of BUMDes Harapan Kita Loa Kulu Kota to improving community economic welfare from the perspective of maqashid sharia. This research employed a descriptive qualitative approach involving 10 purposively selected informants, including the village head, BUMDes managers, staff, business-unit workers, partners/UMKM actors, and benPeraeficiary residents. Data were collected through interviews, observation, and documentation. Welfare indicators included income improvement, job creation, business opportunities, access to economic services, utilization of village assets, and contribution to village revenue. The findings show that vessel piloting services, rice sales, payment services, waste collection, UMKM land rental, and business partnerships created local employment, improved community economic services, and generated the highest net profit of Rp323,566,336 in 2023. From the maqashid sharia perspective, these contributions reflect amanah, ta’awun, justice, maslahah, and hifz al-mal.